PENGARUH KOMPENSASI FINANSIAL DAN NON-FINANSIAL TERHADAP KINERJA KARYAWAN PADA BANK SUMUT KCP SYARIAH SIMPANG KAYU BESAR - Balqis, Amanda; Harmain, Hendra; Nurwani, Nurwani (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
The purpose of this research is to know that financial and non-financial compensation have an influence to employee performance in PT. Bank SUMUT KCP Syariah Simpang Kayu Besar with Parsial and Simultan test. This research is using quantitative method with saturated sampling technique. Using parsial Test (t-test), Simultan test (F test) and coefficient of determination test as analysis technique. The first result show that financial compensation has a significant effect to employee performance partially. The second result show t test > t table (2.497 > 2.048) wich means that non-financial compensation has significant effect to employee performance partially. And the third result show that financial and non-financial compensation have an influence on employee performance simultaneously.